[(68)Ga]Ga-THP-Pam: A Bisphosphonate PET Tracer with Facile Radiolabeling and Broad Calcium Mineral Affinity - Keeling, George P. (Bioconjug Chem, 2021)
Calcium minerals such as hydroxyapatite (HAp) can be detected noninvasively in vivo using nuclear imaging agents such as [(18)F]NaF (available from cyclotrons), for positron emission tomography (PET) and (99m)Tc-radiolabeled bisphospho-nates (BP; available from (99m)Tc generators for single photon emission computed tomography (SPECT) or scintigraphy). These two types of imaging agents allow detection of bone metastases (based on the presence of HAp) and vascular calcification lesions (that contain HAp and other calcium minerals). With the aim of developing a cyclotron-independent PET radiotracer for these lesions, with broad calcium mineral affinity and simple one-step radiolabeling, we developed [(68)Ga]Ga-THP-Pam. Radiolabeling with (68)Ga is achieved using a mild single-step kit (5 min, room temperature, pH 7) to high radiochemical yield and purity (>95%). NMR studies demonstrate that Ga binds via the THP chelator, leaving the BP free to bind to its biological target. [(68)Ga]Ga-THP-Pam shows high stability in human serum. The calcium mineral binding of [(68)Ga]Ga-THP-Pam was compared in vitro to two other (68)Ga-BPs which have been successfully evaluated in humans, [(68)Ga]Ga-NO2AP(BP) and [(68)Ga]Ga-BPAMD, as well as [(18)F]NaF. Interestingly, we found that all (68)Ga-BPs have a high affinity for a broad range of calcium minerals implicated in vascular calcification disease, while [(18)F]NaF is selective for HAp. Using healthy young mice as a model of metabolically active growing calcium mineral in vivo, we compared the pharmacokinetics and biodistribution of [(68)Ga]Ga-THP-Pam with [(18)F]NaF as well as [(68)Ga]NO2AP(BP). These studies revealed that [(68)Ga]Ga-THP-Pam has high in vivo affinity for bone tissue (high bone/muscle and bone/blood ratios) and fast blood clearance (t(1)/(2) < 10 min) comparable to both [(68)Ga]NO2AP(BP) and [(18)F]NaF. Overall, [(68)Ga]Ga-THP-Pam shows high potential for clinical translation as a cyclotron-independent calcium mineral PET radiotracer, with simple and efficient radiochemistry that can be easily implemented in any radiopharmacy.